Unraveling the biosynthesis of quinolizidine alkaloids using the genetic and chemical diversity of Mexican lupins - Ramirez-Betancourt, Astrid; Michelle Hernandez-Sanchez, Arianna; Salcedo-Morales, Guadalupe; Ventura-Zapata, Elsa; Robledo, Norma; Wink, Michael; Bermudez-Torres, Kalina (Diversity, 2021)
Quinolizidine alkaloids (QAs) are synthesized by the genus Lupinus as a defense against herbivores. Synthesis of QAs in lupins is species- and organ-specific. Knowledge about their biosynthesis and their corresponding pathways are still fragmentary, in part because lupins of commercial importance were mainly investigated, representing a small sample of the chemodiversity of the genus. Here, we explore the use of three Mexican lupins: Lupinus aschenbornii, Lupinus montanus, and Lupinus bilineatus as a model to study the physiology of QA biosynthesis. The corresponding QA patterns cover widely and narrowly distributed tetracyclic QAs. Quinolizidine alkaloid patterns of seeds and plantlets at different developmental stages were determined by GLC-MS and compared to identify the onset of de novo QA synthesis and to gain insight into specific and common biosynthesis trends. Onset of de novo QA biosynthesis occurred after the metabolization of seed QA during germination and was species-specific, as expected. A common QA pattern, from which the diversity of QA observed in these species is generated, was not found; however, lupanine and 3 beta-lupanine were found in the three specieswhile sparteine was not found in Lupinus bilineatus, suggesting that this simplest tetracyclic QA is not the precursor of more complex QAs. Similar patterns of metabolization and biosynthesis of structurally related QAs were observed, suggesting a common regulation.